PEMBELAJARAN LAGU TRADISIONAL NUSANTARA DENGAN METODE TUTOR SEBAYA PADA KELAS VIII MADRASAH TSANAWIYAH AL MUTTAQIN SITUMANG SUNGAI AUR PASAMAN BARAT - Alghozali Alghozali; Tulus Handra Kadir; Erfan Erfan (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to 1) to observe and describe the implementation of the application of the method of peer tutors in learning, arts and culture, i.e. the art of music, 2) see successful or whether the application of the method of peer tutors. The research is the research action class (PTK). The object of the research is in the form of people, behavior, or data about an event that can generate information research data. The instruments used are observation, the success rate of students and the camera. The technique of data collection is done by way of documentation, observation and interview.The results showed that the use of different models of peer tutors in learning the art of music in class VIII MTs Al-Muttaqin Situmang Aur River successfully and improve students ' ability in singing the ampar-ampar pisang. Students who are still weak in mastery of material on cycle 1 can be dealt with continue on the second cycle i.e. by strengthening technical mastery against the song and expression of dynamical ampar-ampar pisang with reinforcement through audio visual playback ampar-ampar song shows banana. Thus, the learning process that is implemented on a cycle of 2 States the success rate. Keywords: Learning, Traditional Songs, Peer Tutor Methods